The use of recovery strategies in Gaelic games: A mixed-methods analysis - Daly, L. S.; Catháin, C. Ó.; Kelly, D. T. (International Journal of Sports Physiology and Performance, 2023)
Purpose: This study investigated Gaelic games players` (1) use of postexercise recovery strategies; (2) recovery strategies according to sport, biological sex, and playing standard; and (3) recovery strategy periodization.